ANALISIS PERENCANAAN PENGELOLAAN KEUANGAN DESA BERDASARKAN PERSPEKTIF EKONOMI ISLAM (STUDI KASUS PADA DESA GUNUNG BERKAT KECAMATAN BANDAR PULAU ASAHAN) - Sitorus, Seftia Rendiani; Sudiarti, Sri; Nasution, Muhammad Lathief Ilhamy (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
The planning of the village's financial management will help the village in reducing the failure of activities due to uncertainty, the planning of financial management can also be a tool of supervision and control by the leader, the village chief and the village secretary. The purpose of this research is to analyze the planning of the financial management of the village in Mount Berkat Village. This research approach is descriptive using quantitative data types. Data collection methods are done with library research, interviews, and documentation. The results of this study show that the planning of the financial management of the village of Gunung Berkat is in accordance with the Regulations of the Minister of Home Affairs (Permendagri) No. 20 of 2018.